STAT3 Single Nucleotide Polymorphism rs4796793 SNP Does Not Correlate with Response to Adjuvant IFNα Therapy in Stage III Melanoma Patients - Schrama, David; Ugurel, Selma; Sucker, Antje; Ritter, Cathrin; Zapatka, Marc; Schadendorf, Dirk; Becker, Jürgen Christian (Frontiers in Medicine, 2014)
Interferon alpha (IFNα) is approved for adjuvant treatment of stage III melanoma in Europe and the US. Its clinical efficacy, however, is restricted to a subpopulation of patients while side effects occur in most of treated patients. Thus, the identification of predictive biomarkers would be highly beneficial to improve the benefit to risk ratio. In this regard, STAT3 is important for signaling of the IFNα receptor. Moreover, the STAT3 single nucleotide polymorphism (SNP) rs4796793 has recently been reported to be associated with IFNα sensitivity in metastatic renal cell carcinoma. To translate this notion to melanoma, we scrutinized the impact of rs4796793 functionally and clinically in this cancer. Interestingly, melanoma cells carrying the minor allele of rs4796793 were the most sensitive to IFNα in vitro. However, we did not detect a correlation between SNP genotype and STAT3 mRNA expression for either melanoma cells or for peripheral blood lymphocytes. Next, we analyzed the impact of rs4796793 on the clinical outcome of 259 stage III melanoma patients of which one third had received adjuvant IFNα treatment. These analyses did not reveal a significant association between the STAT3 rs4796793 SNP and patients’ progression free or overall survival when IFN treated and untreated patients were compared. In conclusion, STAT3 rs4796793 SNP is no predictive marker for the efficacy of adjuvant IFNα treatment in melanoma patients.